Grounding activities effectively lower blood pressure in elderly people with hypertension (Nursing and Health Sciences Journal (NHSJ), 2025)
Hypertension is one of the most prevalent chronic conditions worldwide, particularly among elderly populations. The condition of blood pressure that is too high causes the heart to work harder in pumping blood throughout the body, which causes organ damage and several diseases, such as Congestive Heart Failure, Stroke, visual impairment, Heart Failure, Kidney Failure, and other diseases. Prevention of Hypertension can be achieved through both pharmacological and non-pharmacological treatments. Pharmacological treatment with antihypertensive drugs, non-pharmacological ones include doing physical activities, walking barefoot, also called grounding. The purpose of this study was to investigate the effectiveness of grounding on blood pressure in elderly individuals with hypertension. The research design employed a pre-experimental design, with a total of 32 respondents selected through simple random sampling. Blood pressure data was measured 30 minutes before and after grounding. Grounding was conducted over a period of 3 weeks, with sessions held three times a week, each lasting 30 minutes. The average decrease in systolic blood pressure was 7.81 mmHg, and in diastolic blood pressure was 2.66 mmHg. The paired t-test results yielded a p-value of 0.00 < 0.05 (alpha), indicating a significant effect of grounding activities on lowering blood pressure in elderly hypertensive individuals. The results of this grounding activity study suggest that it can be used as a non-pharmacological therapy to lower blood pressure.